Development Status of Dynamic Sealing Technology and Discussion on Advanced Sealing Technologies - Yan Wang; Shuoshuo Niu; Jiahao Zhang; Cong Feng; Yutong Wang; Doudou Shen; Decai Li; Tong Li; Pengcheng Cao; Yufan Zhang (Lubricants)
This paper reviews the current state of dynamic sealing technologies, examining the challenges faced by conventional sealing methods under complex working conditions, such as high temperature, high pressure, and corrosive environments. It also provides a concise overview of the status and developmental trends in sealing inspection technologies. From the perspective of obstruction mechanisms, this study reinterprets the concept of sealing science by redefining the classification of sealing types based on solid-phase medium obstruction, fluid hydrostatic and hydrodynamic obstruction, fluid pumping obstruction, fluid energy dissipation obstruction, and fluid impact obstruction. Comparative analyses of sealing structures across these obstruction mechanisms are presented. The sealing technology based on fluid impact medium obstruction, newly proposed by this paper, represents an innovative sealing approach. It offers distinct advantages such as zero wear, structural simplicity, and high stability, addressing longstanding issues in high-speed, large-clearance non-contact seals, including low leakage suppression efficiency, system complexity, and poor stability. Since its introduction, this novel sealing structure has garnered significant attention and recognition from both the academic and industrial sealing communities. With the potential to revolutionize the field, this groundbreaking sealing design is poised to lead the next wave of technological advancements in sealing science.